2022
DOI: 10.1021/acs.inorgchem.1c03622
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Performance of Perovskite and Metal–Organic Framework Hybrid Material for the Reduction of N2 to Ammonia

Abstract: The orthorhombic phase of KNbO 3 perovskite has been applied for nitrogen (N 2 ) photoreduction to ammonia (NH 3 ). However, this material suffers from a low surface area and low ammonia production efficiency under UV light irradiation. To eliminate these barriers, we used a metal−organic framework (MOF), named as TMU-5 ([Zn(OBA)(BPDH) 0.5 ] n •1.5DMF, where H 2 OBA = 4,4′-oxybis-(benzoic acid) and BPDH = 2,5-bis(4-pyridyl)-3,4-diaza-2,4-hexadiene), for the synthesis of the KNbO 3 @TMU-5 hybrid material. KNbO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…To address this issue, Boukherroub and co-workers coupled MOFs (TMU-5) with significant adsorption potential for N 2 gas molecules with KNbO 3 for photocatalytic N 2 fixation (Figure 5b). 113 TMU-5 not only acts as a MOF material with good porosity but also can achieve excellent photocatalytic performance by enhancing light absorption, charge separation, and reactant activation. The NH 3 formation rate of KNbO 3 @TMU-5 is 39.9 μmol L −1 h −1 g −1 , which is much higher than that of KNbO 3 under the same experimental conditions.…”
Section: Mof-based Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…To address this issue, Boukherroub and co-workers coupled MOFs (TMU-5) with significant adsorption potential for N 2 gas molecules with KNbO 3 for photocatalytic N 2 fixation (Figure 5b). 113 TMU-5 not only acts as a MOF material with good porosity but also can achieve excellent photocatalytic performance by enhancing light absorption, charge separation, and reactant activation. The NH 3 formation rate of KNbO 3 @TMU-5 is 39.9 μmol L −1 h −1 g −1 , which is much higher than that of KNbO 3 under the same experimental conditions.…”
Section: Mof-based Compositesmentioning
confidence: 99%
“…112 Copyright 2019 Elsevier B.V. (b) Combination of PXRD patterns of KNbO 3 @TMU-5 and the components. Reproduced with permission 113. Copyright 2022 American Chemical Society.…”
mentioning
confidence: 99%
“…Most ternary metal oxides first used for photocatalytic nitrogen fixation are titanate or Bi-based oxide systems (Chen et al, 2018;Huang et al, 2020). Higher conversion efficiency for mingled transition metal composite oxides such as Sb 2 MoO 6 (Mousavi et al, 2022), SrMoO 4 (Luo et al, 2019), LaCoO 3 (Haiguang Zhang et al, 2019), CoFe 2 O 4 (Zheng et al, 2020), Ni 3 V 2 O 8 (Vesali-Kermani et al, 2020b), KNbO 3 (Xing et al, 2019;Xing et al, 2020;Chamack et al, 2022), LiNbO 3 (Xiazhang Li et al, 2020), have been reported compared to corresponding monometallic oxides. Most mixed metal oxides are perovskite oxide compounds with wide bandgaps (Zejian .…”
Section: Polymetallic Oxidesmentioning
confidence: 99%
“…All samples depended on KTa 0.75 Nb 0.25 O 3 to provide the photo/piezogenerated electrons for promoting spatial charge separation, which likely played a dominant role for nitrogen fixation. A pioneering study that coupled conventional KNbO 3 with photoactive MOFs was conducted by Chamack et al ( Chamack et al, 2022 ). Introduction of ([Zn(OBA) (BPDH) 0.5 ] n ·1.5DMF (TMU-5) enhanced the photocatalytic performance owing to the porosity, high surface area, and higher density of negative charges on Nb sites observed by N 2 adsorption/desorption isotherms and XPS scans, respectively ( Figures 9A,B ).…”
Section: Tungsten-based and Related Photocatalysts For Nrrmentioning
confidence: 99%
See 1 more Smart Citation